Model Problem Based Learning untuk Meningkatkan Keterampilan Literasi Sosial - Zelvira Pebriyanti; Muhaiminah Jalal (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to improve the social literacy skills of fourth-grade students at SD 145/IV Salam Buku I, Batangmasumai District, Merangin Regency, which are still considered low. Students are not yet actively connecting science and natural sciences material to their surrounding social conditions and have difficulty understanding and critically analyzing social issues. This study used the Classroom Action Research (CAR) method with the Problem-Based Learning (PBL) model, implemented in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. Data collection instruments included teacher and student activity observation sheets, field notes, and documentation, which were analyzed descriptively using qualitative and quantitative methods. The results showed that the implementation of the PBL model was effective in improving students' social literacy skills. In the first cycle, students' social literacy skills reached 68%, and increased to 85% in the second cycle, representing a 17% increase. In conclusion, Problem-Based Learning (PBL) is capable of improving students' social literacy skills in science and natural science learning. This model is recommended as an active and contextual learning strategy that encourages comprehensive student engagement in understanding social issues around them.